Characterization of 18F-PM-PBB3 (18F-APN-1607) Uptake in the rTg4510 Mouse Model of Tauopathy - Chi-Chang Weng; Ing-Tsung Hsiao; Qing-Fang Yang; Cheng-Hsiang Yao; Chin-Yin Tai; Meng-Fang Wu; Tzu-Chen Yen; Ming-Kuei Jang; Kun-Ju Lin (Molecules, 2020)
Misfolding, aggregation, and cerebral accumulation of tau deposits are hallmark features of Alzheimer’s disease. Positron emission tomography study of tau can facilitate the development of anti-tau treatment. Here, we investigated a novel tau tracer 18F-PM-PBB3 (18F-APN-1607) in a mouse model of tauopathy. Dynamic PET scans were collected in groups of rTg4510 transgenic mice at 2–11 months of age. Associations between distribution volume ratios (DVR) and standardized uptake value ratios (SUVR) with cerebellum reference were used to determine the optimal scanning time and uptake pattern for each age. Immunohistochemistry staining of neurofibrillary tangles and autoradiography study was performed for ex vivo validation. An SUVR 40–70 min was most consistently correlated with DVR and was used in further analyses. Significant increased 18F-PM-PBB3 uptake in the brain cortex was found in six-month-old mice (+28.9%, p < 0.05), and increased further in the nine-month-old group (+38.8%, p < 0.01). The trend of increased SUVR value remained evident in the hippocampus and striatum regions except for cortex where uptake becomes slightly reduced in 11-month-old animals (+37.3%, p < 0.05). Radioactivity distributions from autoradiography correlate well to the presence of human tau (HT7 antibody) and hyperphosphorylated tau (antibody AT8) from the immunohistochemistry study of the adjacent brain sections. These findings supported that the 40–70 min 18F-PM-PBB3 PET scan with SUVR measurement can detect significantly increased tau deposits in a living rTg4510 transgenic mouse models as early as six-months-old. The result exhibited promising dynamic imaging capability of this novel tau tracer, and the above image characteristics should be considered in the design of longitudinal preclinical tau image studies.